11C‐Acetylation of Amines with [11C]Methyl Iodide with Bis(cyclopentadienyldicarbonyliron) as the CO Source. Issue 38 (11th October 2017) - Dahl, Kenneth; Nordeman, Patrik
Abstract : We describe herein a novel approach for the direct 11 C‐acetylation of amines. The carbonylative protocol is palladium‐mediated, uses bis(cyclopentadienyldicarbonyliron) as the CO source, and [ 11 C]methyl iodide or [ 11 C]methyl iodide‐D3 as a radioactive precursor. A set of functionalized primary and secondary amines was 11 C‐labelled in radiochemical yields ranging from 7–85 %. The potential use of this method for positron emission tomography radiotracer production was additionally demonstrated by the radiosynthesis of [ 11 C]lacosamide, [ 11 C]melatonine, and [ 11 C]acecainide in 44–55 % RCY. Abstract : An approach for the direct 11 C‐acetylation of amines is presented. The carbonylative protocol uses palladium as mediator, relies upon bis(cyclopentadienyldicarbonyliron) as the carbon monoxide source and incorporate [ 11 C]methyl iodide or [ 11 C][D3 ]methyl iodide as the radioactive precursor. A set of functionalized primary and secondary amines was 11 C‐labelled in radiochemical yields ranging from 7–85 %.